Comparison of the efficacies of disinfectants to control microbial contamination in dental unit water systems in general dental practices across the European Union - Schel, A J; Marsh, P D; Bradshaw, D J; Finney, M; Fulford, M R; Frandsen, E; Østergaard, E; ten Cate, J M; Moorer, W R; Mavridou, A; Kamma, J J; Mandilara, G; et al. (Applied and environmental microbiology, 2006)
Water delivered by dental unit water systems (DUWS) in general dental practices can harbor high numbers of bacteria, including opportunistic pathogens. Biofilms on tubing within DUWS provide a reservoir for microorganisms and should be controlled. This study compared disinfection products for their ability to meet the American Dental Association's guideline of <200 CFU x ml(-1) for DUWS water. Alpron, BioBlue, Dentosept, Oxygenal, Sanosil, Sterilex Ultra, and Ster4Spray were tested in DUWS (n = 134) in Denmark, Germany, Greece, Ireland, The Netherlands, Spain, and the United Kingdom. Weekly water samples were tested for total viable counts (TVCs) on yeast extract agar, and, where possible, the effects of products on established biofilm (TVCs) were measured. A 4- to 5-week baseline measurement period was followed by 6 to 8 weeks of disinfection (intermittent or continuous product application). DUWS water TVCs before disinfection ranged from 0 to 5.41 log CFU x ml(-1). Disinfectants achieved reductions in the median water TVC ranging from 0.69 (Ster4Spray) to 3.11 (Dentosept) log CFU x ml(-1), although occasional high values (up to 4.88 log CFU x ml(-1)) occurred with all products. Before treatment, 64% of all baseline samples exceeded American Dental Association guidelines, compared to only 17% following commencement of treatment; where tested, biofilm TVCs were reduced to below detectable levels. The antimicrobial efficacies of products varied (e.g., 91% of water samples from DUWS treated with Dentosept or Oxygenal met American Dental Association guidelines, compared to 60% of those treated with Ster4Spray). Overall, the continuously applied products performed better than those applied intermittently. The most effective products were Dentosept and Oxygenal, although Dentosept gave the most consistent and sustained antimicrobial effect over time.